Association between low-fat diet and liver cancer risk in 98,455 participants: Results from a prospective study - Peng, Linglong; Xiang, Ling; Xu, Zhiquan; Gu, Haitao; Zhu, Zhiyong; Tang, Yunhao; Jiang, Yahui; He, Hongmei; Wang, Yaxu; Zhao, Xiaodong (Frontiers in Nutrition, 2022)
Background: Low-fat diet reduces the risk of chronic metabolic diseases such as obesity and diabetes, which exhibit overlapping mechanisms with liver cancer. However, the association between low-fat diet and liver cancer risk remains unclear. Aim: To investigate whether adherence to low-fat diet is associated with a reduced risk of liver cancer in a prospective study. Methods: Data of participants in this study were collected from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial. A low-fat diet score was calculated to reflect adherence to low-fat dietary pattern, with higher scores indicating greater adherence. Cox regression was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for liver cancer incidence with adjustment for potential covariates. Restricted cubic spline model was used to characterize liver cancer risk across the full range of the low-fat diet score. Prespecified subgroup analyses were used to identify potential impact modifiers. Sensitivity analyses were performed to test the robustness of this association. Results: A total of 98,455 participants were included in the present analysis. The mean (standard deviation) age, low-fat diet score, and follow-up time were 65.52 (5.73) years, 14.99 (6.27) points, and 8.86 (1.90) years, respectively. During 872639.5 person-years of follow-up, 91 liver cancers occurred, with an overall incidence rate of 0.01 cases per 100 person-years. In the fully adjusted Cox model, the highest versus the lowest quartile of low-fat diet score was found to be associated with a reduced risk of liver cancer (HRQ4 vs Q1: 0.455; 95% CI: 0.216, 0.956; P = 0.032 for trend), which remained associated through a series of sensitivity analyses. The restricted cubic spline model showed a linear dose–response association between low-fat diet score and liver cancer incidence (p = 0.482 for nonlinear). Subgroup analyses did not show significant interaction between low-fat diet score and potential impact modifiers in the incidence of liver cancer. Conclusion: In this study, low-fat diet score is associated with reduced liver cancer risk in the US population, indicating that adherence to low-fat diet may be helpful for liver cancer prevention. Future studies should validate our findings in other populations.